2002
DOI: 10.1177/000841740206900304
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Reimbursement Systems on Occupational Therapy Practice in Canada and the United States of America

Abstract: Different funding and cost-control mechanisms in Canada and the United States of America (USA) have a powerful influence on occupational therapy practice in each country. Canada's public health insurance system emphasizes access to health care services based on medical need. Costs are controlled at the provincial government level by limiting the capacity of facilities and personnel. Occupational therapists in publicly-funded settings have considerable professional autonomy to use occupational therapy theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…An occupational therapist assists a patient to engage in occupations, in order to ultimately enhance occupational performance or efficiency, and to achieve health through doing. Other authors have also identified the difficulty of enacting occupation‐focused therapy within medically dominated health services (Baum, Berg, Seaton & White, 2002; Bryden & McColl, 2003; Crabtree, 1998a; Jongbloed & Wendland, 2002; Pollard & Walsh, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…An occupational therapist assists a patient to engage in occupations, in order to ultimately enhance occupational performance or efficiency, and to achieve health through doing. Other authors have also identified the difficulty of enacting occupation‐focused therapy within medically dominated health services (Baum, Berg, Seaton & White, 2002; Bryden & McColl, 2003; Crabtree, 1998a; Jongbloed & Wendland, 2002; Pollard & Walsh, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…While exciting, this vision is a departure from the occupational therapy that had emerged over the years, an occupational therapy that was generally organized along clinically defined programmatic areas (Baum, Berg, Seaton, & White, 2002;Jongbloed & Wendland, 2002) and had become focused on a component approach to remediation of specific medical problems (Wilcock, 1991;Yerxa, 1993), particularly in teaching hospitals where medical referral is still required.…”
mentioning
confidence: 99%
“…Although there was no evidence in this study to suggest that occupational therapists' home recommendations for either equipment or home modifications were unjustifiably influenced by patient health insurance type, the fact remains that patients with Medicaid and Medicare insurance were discharged home with lower levels of function and had more limited ability to pay for equipment and modifications. In this way, the results of this study point out how deeply health policies penetrate clinical decision-making on a day-to-day basis and speak to the personal tensions that are experienced by therapists whose professional training has prepared them to address functional challenges at the individual level (Walker, 2000), and not policy challenges at the ideological level (Jongbloed & Wendland, 2002). Lohman and Brown (1997) address the issue of therapists' ethical obligations and moral stance in the particular context of managed care and urge clinicians to vigorously represent and advocate for patients-not only in direct service situations, but at policy levels as well.…”
Section: Resultsmentioning
confidence: 81%